2007
DOI: 10.1007/s00125-007-0707-z
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative mutant forms of the cAMP response element binding protein induce apoptosis and decrease the anti-apoptotic action of growth factors in human islets

Abstract: Aims/hypothesis Transplantation of islets is a viable option for the treatment of diabetes. A significant proportion of islets is lost during isolation, storage and after transplantation as a result of apoptosis. cAMP response element binding protein (CREB) is an important cell survival factor. The aim of the present study was to determine whether preservation of CREB function is needed for survival of human islets. Materials and methods To determine the effects of downregulation of CREB activity on beta cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…8). Previously, we have reported that CREB is needed for the anti-apoptotic effects of exendin-4 [19]. Thus the present study suggests that a combination of exendin-4 and phosphodiesterase 3 and 4 inhibitors could decrease islet inflammation in addition to improving beta cell mass in patients with diabetes.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…8). Previously, we have reported that CREB is needed for the anti-apoptotic effects of exendin-4 [19]. Thus the present study suggests that a combination of exendin-4 and phosphodiesterase 3 and 4 inhibitors could decrease islet inflammation in addition to improving beta cell mass in patients with diabetes.…”
Section: Discussionsupporting
confidence: 59%
“…8a). CREB, an anti-apoptotic transcription factor that mediates the effects of exendin-4, is phosphorylated by cyclic AMP-activated protein kinase A (PKA) [19]. Therefore we determined the levels of phosphorylated CREB as a measure of increase in cyclic Human islets (2,000 islet equivalents) were pre-incubated with 100 nmol/l of exendin-4 (Ex), 15 μmol/l rolipram (R), 10 μmol/l cilostamide (C), 1 mmol/l DBC, 15 μmol/l Bay 11-7085 (Bay) and 1 μmol/l JAK inhibitor (JI) as indicated for 30 min, followed by exposure to a combination of 2 ng/ml each of IL-1β, TNF-α and IFN-γ (Cyt) for 6 h. Total RNA was isolated and PCR-based expression profiling of genes specific to the inflammatory pathway was carried out *p<0.05, **p<0.01 and ***p<0.001…”
Section: Regulation Of Cxcl10 Production By Cytokines In Min6 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cAMP/PKA/CREB cascade represents a central mechanism of GLP-1 action, specifically when this relates to promotion of beta cell survival [47], even though other signalling mediators may also be implicated [48,49]. Impairment of CREB-mediated transcription led to loss of islets by apoptosis and diminished the antiapoptotic action of exendin-4 in human islets [50]. In line with these results, our previous studies demonstrated that inhibition of TNF-α-induced JNK phosphorylation by exendin-4 was abrogated when cells were preincubated with H89, a specific inhibitor of PKA [15].…”
Section: Discussionmentioning
confidence: 99%
“…So far, initial studies testing the potential to target CREB as a strategy for cancer therapy have focused on approaches that inhibit CREB function by shRNAs or by using dominant-negative CREB mutants, which target the CREB-CBP interaction, thereby preceding the CREB-dependent transcriptional activation of gene expression. Indeed, inhibition of CREB activity by dominant-negative mutants or by shRNAs was associated with a reduced in vitro and in vivo growth potential and increased radiosensitivity (39,43,44). In the HER-2/neu model used, shCREB-mediated inhibition also resulted in decreased proliferation of HER-2/neu þ cells, accompanied by cell-cycle arrest, increased apoptosis, and reduced cell migration and invasion, which was directly associated with an altered expression of proapoptotic and antiapoptotic genes as well as a transcriptional downregulation of MMP-2 and -9 expression.…”
mentioning
confidence: 99%